The practice of authentic assessment in an EFL speaking classroom - Nurul Inayah; Endang Komariah; Abdin Nasir (Universitas Syiah Kuala, 2019)
The implementation of Curriculum 2013 has inserted the authentic assessment as the measurement method to evaluate students’ learning objectives and achievements in the classroom. In this curriculum, the application of authentic assessment requires teachers to evaluate students’ in three competencies: attitude, knowledge, and skill. Most teachers claim that speaking is the most difficult skill to be assessed by using the authentic assessment, considering the complex features of the assessment. This research was aimed at describing the application of authentic assessment in a speaking classroom which relates to the types of the assessment and the scoring rubric. The subjects of the study were an English teacher and 28 students of a class at one of the junior high schools in Banda Aceh. Under the descriptive qualitative approach umbrella, the data in this study was obtained from observation and document analysis. The results of the study revealed that the teacher used several types of activities to assess students’ speaking skills: (1) attitude assessment (teacher observation), (2) knowledge assessment (teacher interview/short answer question), and (3) skill assessment (narrating sequences). The result of this study indicates that authentic assessment is a feasible way to assess students’ speaking skill and it should be employed in assessing other skills as well for learning languages.